Análisis de la sostenibilidad y competitividad de las empresas turísticas de alimentos y bebidas del cantón Salcedo, provincia de Cotopaxi. - Alvarez Pacheco, Erika Lucia (2023)
The present research work was carried out in Salcedo canton, Cotopaxi province with the objective to analyze sustainability and competitiveness, through inferential statistics to propose improvement strategies in food and beverage tourism companies, to which raised specific objectives and activities that were developed according to a schedule. Through the tourist registry of companies, 24 establishments were identified as study population. To evaluate sustainability variable, the InnovaRSE methodology was used, which has a total of 30 statements divided into 10 for each of its dimensions (Social, economic and environmental). Then, to measure competitiveness of the companies, the IDB Map methodology was used, consisting on 103 questions addressed to each area and subarea of companies (strategic planning, value chain, quality assurance, accounting and finance, environmental management, merchandising, human talent and information systems). Finally, the last objective, the information was systematized in an Excel spreadsheet in order to create descriptive statistical tables. Where, the competitiveness variable resulted in 3 companies that are within a range of 21% to 40% with low competitiveness categorization, these being the companies with a high value in the strategic areas planning, quality assurance and value chain. On the other hand, it was possible to show that 16 companies are in a range of 0% to 20% with a category of very low competitiveness due to shortcomings in areas and subareas corresponding to evaluated variable. While, in the sustainability analysis, 12 companies obtained a score of 4 to 6 within Improvement Processes and 7 companies achieved a score of 1 to 3 within improvement areas due to lack compliance in evaluated dimensions. A correlation test was also carried out with two variables using the SPSS software, obtaining a result of 0.60, which indicates that there is no correlation between sustainability and competitiveness because there has been no interest in improving dimensions and evaluated areas. Finally, a SWOT analysis was carried out by identifying internal and external factors with the MEFI, MEFE, Valuation and Strategies matrices according to their impact degree: High, medium or low. Obtaining as a result 16 improvement strategies that can be implemented in companies. In conclusion, by proposing improvement strategies, companies could put sustainability into practice and thereby improve their competitive level.